Incidence and management of rhinosinusitis after complex orbitofacial reconstruction. (7th November 2013) - Parkes, William J.; Nyquist, Gurston G.; Rizzi, Christopher; Zhang, Sarah; Evans, James J.; Heffelfinger, Ryan N.; Rosen, Marc R.; Curry, Joseph M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To examine the sinus‐related sequelae of free flap reconstruction for complex orbitofacial defects. Study Design Retrospective chart review. Methods Demographic, clinical, and radiographic data on a series of 55 patients who had undergone free tissue transfer for orbitofacial reconstruction was retrospectively reviewed. Follow‐up of ≥ 3 months was available for 49 patients. Outcome measures studied included clinical or radiographic evidence of sinusitis and the need for sinus surgery. Results The most commonly involved sinuses were the ethmoid (n = 40) and maxillary (n = 38) sinuses, and the anterolateral thigh was the most common flap used (n = 41). Clinical and/or radiographic sinusitis was evident in 21 patients (43%), and 10 patients (20%) required sinus surgery at some point during follow‐up. Involvement of multiple sinuses in the initial orbitofacial surgery was associated with a significantly increased need for subsequent sinus surgery (P = 0.009). Adjuvant radiotherapy and adjuvant chemoradiotherapy were associated with a significantly increased risk for the development of rhinosinusitis (P = 0.045 and 0.016, respectively). Conclusion Rhinosinusitis and the need for operative management of sinus obstruction are common in patients having undergone complex orbitofacial reconstruction. Careful management of the paranasal sinuses is an important component of the multidisciplinary treatment of such patients. Level of Evidence 4. Laryngoscope, 124:1059–1065, 2014